Association of Aldosterone and Cortisol with Cardiovascular Risk Factors in Prehypertension Stage - Sadiqa Badar Syed; Masood Anwar Qureshi (International Journal of Hypertension)
Background. The Pakistani population has higher incidence of cardiovascular (CV) diseases at younger ages, due to undiagnosed, uncontrolled hypertension (HTN). A variety of associated HTN stressors is also reported. The study plans to understand the variables associated with initiation of HTN in this population. Objective. To find plasma aldosterone and cortisol relationship with some CV risk factors (obesity, dyslipidemia, hyperglycemia, sodium and potassium) in different stages of HTN particularly prehypertension. Subjects and Methods. The study conducted on 276 subjects (25–60 years), classified into prehypertensive (𝑛=55), HTN stage-1 (𝑛=70) and II (𝑛=76) according to 7th JNC report and compared with normotensive controls (𝑛=75). The anthropometric profiles (height, weight, waist circumference, Body Mass index) and BP recorded. Serum cortisol, aldosterone, total cholesterol, Low density lipoproteins, blood glucose, Na+ and K+, using standard laboratory techniques, were determined in fasting blood samples. Results. Subjects were mostly overweight and obese (80%, 90%, and 76% in pre-HTN, stage-I and II versus 69% in controls). The aldosterone level (ng/dl) was in higher normal range (9.17–12.41) and significantly correlated to BMI (0.587) in controls, and to TC (0.726) and LDL (0.620) in pre-HTN stage-I. The cortisol level was positively correlated (𝑃<0.01) to BMI (0.538), Na+ (0.690) and K+ (0.578) in control, and to BMI (0.628) and WC (0.679) in pre-HTN group, showing its association with BMI>25. Conclusion. Pre-HTN stage among Pakistani population with successive increase in various risk factors of HTN in relation to aldosterone and cortisol has been identified. Interaction of the risk factors with endogenous levels of these hormones may initiate stages of HTN.